The use of growth models to evaluate the changing response to digestible lysine in high-lean growth gilts - Friesen, K.G.; Schinckel, A.P.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Conventional response criteria for amino acid research include mean live weight gain and tissue accretion rates over a given weight interval. However, these methods fail to characterize the changing response of tissue accretion to dietary amino acids as body weight increases. For this reason, growth modeling was used to characterize the response to digestible lysine in two experiments (114 gilts each) from 80 to 160 lb and 160 to 300 lb, respectively. Corn-soybean meal diets were formulated to assure that lysine (.54 to 1.04% and .54 to .94% digestible lysine for Exp 1 and 2, respectively) was the first limiting amino acid. Analysis of variance was used to test linear and quadratic responses in cumulative weight gain on test as digestible lysine increased. A time by digestible lysine interaction was detected, indicating that a separate regression equation for each lysine level was necessary. In Exp. 1, ADG and carcass CP accretion were maximized for gilts fed 1.04, .94, and .84% digestible lysine from 80 to 100 lb, 100 to 120 lb, and 120 to 160 lb, respectively. Lipid accretion .74 to .84% digestible lysine. In Exp. 2, ADG was maximized by feeding .84% from 160 to 205 lb and .74% from 205 to 300 lb. Carcass CP accretion was maximized by feeding .94% digestible lysine, and lipid accretion was minimized for gilts fed .84% digestible lysine from 160 to 300 lb. If feeding graded levels of digestible lysine resulted in parallel lines for carcass protein accretion, mean values would result in accurate data evaluation. However, responses to digestible lysine changed over the feeding period. Therefore, the use of BW and compositional growth curves offers an innovative approach to more accurately characterize the growing pig's response to increased digestible lysine.
Keywords: Swine; Pigs; Gilts; Carcass composition; Growth modeling; Growth